Teori Belajar Al-Māwardi: Studi Analisis Tujuan dan Indikator Keberhasilan Belajar - Nurhayati AR; Syahrizal Syahrizal (Ulumuna, 2014)
Al-Māwardi’s concept of learning goals and indicators have rarely been studied and developed in the context of modern education. This article examines the learning goals and indicators of successful education in the thoughts of al-Māwardi and analyzes its relevance to modern education. According to al-Mawardi, successful education can be achieved when students can memorize, understand, know the purpose of learning and practice what they have learnt, and when these indicators shape students’ cognitive, affective, and psychomotor domains. He maintained that these learning processes must be based on a sound faith. This article demonstrates that these objectives and indicators of successful learning proposed by al-Mawardi are very relevant to modern education. Faith based education helps increase student’s belief and discards worldly-oriented education that tend to produce materialistically individualistic people.